Exploration of the Teaching Mode of the “Flipped Classroom” in Art Appreciation Courses in Ordinary Universities - Yang, Jingqi; Li, Zhenghua (Journal of Educational Research and Policies, 2025)
Against the backdrop of continuous social development and deepening educational reforms, traditional teaching models are no longer able to meet the demands of students in the new era. The student-centered teaching model, known as the flipped classroom, is quietly emerging. The flipped classroom is supported by the openness and interactivity of the internet, expands the teaching space, redefines its concept, and effectively integrates the online learning mode with the traditional classroom teaching mode, which can effectively improve students’ learning motivation. This article takes the art appreciation course of public art education at ordinary universities as a case study to discuss the essence and connotation of the flipped classroom. In response to the problems that currently arise in the teaching process of art appreciation courses and the characteristics of art appreciation courses, a flipped classroom teaching model is constructed, which is helpful for changing the current situation of public art education in ordinary universities and for informing the construction of public art education in ordinary universities.